2016
DOI: 10.1074/jbc.m116.735431
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding Ensembles Determine Graded Agonist Efficacies at a G Protein-coupled Receptor

Abstract: G protein-coupled receptors constitute the largest family of membrane receptors and modulate almost every physiological process in humans. Binding of agonists to G protein-coupled receptors induces a shift from inactive to active receptor conformations. Biophysical studies of the dynamic equilibrium of receptors suggest that a portion of receptors can remain in inactive states even in the presence of saturating concentrations of agonist and G protein mimetic. However, the molecular details of agonist-bound ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 70 publications
6
89
0
Order By: Relevance
“…[5] Such ligands are able to overcome the problem of subtype selectivity for the M 1 subtype by making use of cooperativity in the selective binding and activation of the receptor. [6] To take this concept one step further, dualsteric (or bitopic) ligands are developed herein that covalently connect ah igh-affinity/low-selectivity orthosteric moiety to highly selective allosteric building blocks for concomitant interac- tion with both binding sites.R ecently,o ur groups have reported several sets of dualsteric M 1 and M 2 agonists for which dynamic ligand binding is assumed, leading to partial agonism for the M 1 receptor ( Figure 1) [7] as well as for the M 2 receptor. [8] Based on these findings,d ualsteric ligands hold great potential both as future therapeutics and as pharmacological tools owing to their unprecedented selectivity at Mreceptor subtypes,t heir specificity for signaling pathways ("biased signaling"), their capability for partial agonism, and their potential for studying the process of receptor activation at the molecular level.…”
mentioning
confidence: 99%
“…[5] Such ligands are able to overcome the problem of subtype selectivity for the M 1 subtype by making use of cooperativity in the selective binding and activation of the receptor. [6] To take this concept one step further, dualsteric (or bitopic) ligands are developed herein that covalently connect ah igh-affinity/low-selectivity orthosteric moiety to highly selective allosteric building blocks for concomitant interac- tion with both binding sites.R ecently,o ur groups have reported several sets of dualsteric M 1 and M 2 agonists for which dynamic ligand binding is assumed, leading to partial agonism for the M 1 receptor ( Figure 1) [7] as well as for the M 2 receptor. [8] Based on these findings,d ualsteric ligands hold great potential both as future therapeutics and as pharmacological tools owing to their unprecedented selectivity at Mreceptor subtypes,t heir specificity for signaling pathways ("biased signaling"), their capability for partial agonism, and their potential for studying the process of receptor activation at the molecular level.…”
mentioning
confidence: 99%
“…Disingrini et al, 2006) We found that these hybrid compounds are characterized by a truly bitopic (orthosteric and allosteric) binding mode (hence the term "dualsteric" ligands), (Antony et al, 2009) as well as other distinctive features when compared to their parent compounds, such as receptor subtype selectivity and biased agonism. (Bock et al, 2016;De Min et al, 2017) We also demonstrated that some of these hybrid compounds display interesting pharmacological properties, (Cristofaro et al, 2018;Riefolo et al, 2019) including remarkable analgesic effects in vivo in mice. Noteworthy, one of these compounds, from now on named Iper-8-N ( Figure 1, compound 8b in the reporting article), even combined the potent antinociceptive activity with the absence of relevant cholinergic side effects.…”
Section: Introductionmentioning
confidence: 79%
“…Atropine either moves out of the M 3 receptor or into the orthosteric site, as is also evident from the on‐rate of atropine which is about 10 times faster than that of tiotropium (Dowling & Charlton, ). Previously, dual binding at both binding sites was described for the M 2 receptor, were one ligand occupied both sites (Bock et al, ). M 2 receptors are not involved in airway smooth muscle contraction, which is solely mediated via M 3 receptors (Roffel et al, ).…”
Section: Discussionmentioning
confidence: 99%